The Effect of Traditional Games on the Development of Patriotism Character in Children Aged 5-6 Years - Riska Wulandari; Bukman Lian; Rahmah Novianti (Kumara Cendekia, 2026)
This study was motivated by the importance of instilling a sense of patriotism from an early age through enjoyable activities that are aligned with children’s developmental characteristics. The aim of this study is to examine the effect of traditional games on the development of patriotism in children aged 5-6 years. This research employed a quantitative experimental method with sampe of 20 students. The results indicate that traditional games have a significant effect on enhancing children’s patriotism, as evidenced by the hypothesis testing results, where the calculated t-value (22,568) is greater than the t-table value (1,729). The improvement in children’s abilities after the treatment shows that through traditional games, children can learn to preserve culture, develop a sense of care, and build togetherness with peers and their environment. These findings are beneficial for early childhood education as an alternative strategy that is both effective and enjoyable in fostering character values, particularly patriotism, through contextual and culturally based play activities.